2019
DOI: 10.3389/fpsyt.2019.00756
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Connectivity of Striatum Based on the Integrated Connectivity Model in First-Episode Schizophrenia

Abstract: Background: The human striatum is a heterogeneous structure involved in diverse functional domains that related to distinct striatum subregions. Striatal dysfunction was thought to be a fundamental element in schizophrenia. However, the connectivity pattern of striatum solely based on functional or structural characteristics leads to inconsistent findings in healthy adult and also schizophrenia. This study aims to develop an integrated striatal model and reveal the altered functional connectivity pattern of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…Decreased FC of NAcc with the frontal cortices (e.g., right superior frontal gyrus and inferior frontal gyrus) and anterior cingulate gyrus was also observed in patients at baseline relative to controls. The results are consistent with previous studies that reported hypoconnectivity of the frontostriatal loop in schizophrenia ( 18 , 54 ). Specifically, Broca's region and its right hemisphere counterpart in the inferior frontal gyrus are involved in language processing ( 55 , 56 ).…”
Section: Discussionsupporting
confidence: 93%
“…Decreased FC of NAcc with the frontal cortices (e.g., right superior frontal gyrus and inferior frontal gyrus) and anterior cingulate gyrus was also observed in patients at baseline relative to controls. The results are consistent with previous studies that reported hypoconnectivity of the frontostriatal loop in schizophrenia ( 18 , 54 ). Specifically, Broca's region and its right hemisphere counterpart in the inferior frontal gyrus are involved in language processing ( 55 , 56 ).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, while the consistent identification of disrupted dorsal CST and hippocampal-striatal FC across the psychosis continuum aligns with preclinical models emphasizing cortical and hippocampal control over dopamine signalling (23,60,61,(68)(69)(70)97,104), the fMRI findings do not allow us to determine whether cortical or hippocampal abnormalities are primary. Indeed, it is possible that hippocampal dysregulation is linked to a diminished influence from cortex, given that reduced FC between the medial PFC and the hippocampus has been reported only in people with clinically diagnosable illness (i.e., FEP and schizophrenia patients); in this sense, disrupted cortico-hippocampal communication may be a trigger for clinically significant symptom expression by altering hippocampal regulation over dopamine transmission (136,(179)(180)(181)(182). It is also important to note that, due to the small size of the midbrain, wholebrain fMRI studies have limited sensitivity for mapping effects in this region unless they specifically try to investigate the area.…”
Section: Evidence Of Cst Dysconnectivity In Human Neuroimaging Studiesmentioning
confidence: 99%
“…The role of the basal ganglia in schizophrenic patients has been previously observed, particularly the decrease in connectivity between the salience network and the basal ganglia 38 , 39 and the decreased connectivity between the cerebellum and basal ganglia 40 . Similarly, the importance of the thalamus in schizophrenia, identified when using the AAL atlas, is well-known 41 , 42 .…”
Section: Discussionmentioning
confidence: 78%